Circular RNA circ-102,166 acts as a sponge of miR-182 and miR-184 to suppress hepatocellular carcinoma proliferation and invasion - Li, Rong; Deng, Yinan; Liang, Jinliang; Hu, Zhongying; Li, Xuejiao; Liu, Huanyi; Wang, Guoying; Fu, Binsheng; Zhang, Tong; Zhang, Qi; Yang, Yang; Chen, Guihua; et al. (Cellular oncology (Dordrecht), 2021)
Purpose Multiple circular RNAs (circRNAs) have been reported to be dysregulated in hepatocellular carcinoma (HCC). However, their functions and modes of action are still largely unclear. Identifying key circRNAs and revealing their potential functions and molecular mechanisms is considered important for improving the diagnosis and treatment of HCC. Methods Dysregulated circRNAs in HCC were identified through integration of three human HCC circRNAs microarray datasets (GSE94508, GSE97332 and GSE 78520), followed by qRT-PCR validation in primary HCC tissues and cell lines. circRNA characteristics were verified through Sanger sequencing, RNase R treatment, northern blotting and intracellular localization analyses. In addition, circRNA functions in HCC development were assessed using CCK8, colony formation, EDU incorporation, flow cytometry, transwell and scratch wound healing assays in vitro and tumor xenograft assays in vivo. Next, underlying molecular mechanisms in HCC were assessed using dual-luciferase reporter, RNA pull-down, RNA immunoprecipitation and western blotting assays. Results We found that a novel circular RNA, circ-102,166, was down-regulated in HCC and that its expression level was significantly associated with multiple clinicopathologic characteristics, as well as the clinical prognosis of HCC patients. In vitro and in vivo experiments revealed that circ-102,166 overexpression significantly inhibited the proliferation, invasion, migration and tumorigenicity of HCC cells. Furthermore, we found that circ-102,166 can bind to miR-182 and miR-184 to regulate the expression of several of their downstream targets (FOXO3a, MTSS1, SOX7, p-RB and c-MYC). Conclusion Our data revealed a tumor-suppressing role of circ-102,166 in HCC. Down-regulation of circ-102,166 enhanced the proliferation and invasion of HCC cells by releasing the oncomiRs miR-182 and miR-184.